Fatty Acids from Pool Lipids as Possible Precursors of the Male Marking Pheromone in Bumblebees - Edita Kofroňová; Adam Nekola; Josef Cvačka; Jiří Kindl; Irena Valterová (Molecules, 2014)
Triacylglycerols (TGs) stored in the fat bodies of bumblebee males have a species-specific composition. The striking structural similarities between TG fatty acids (FAs) and components of the male marking pheromone in certain species led to the hypothesis that FAs may serve as precursors in pheromone biosynthesis. Here, we analysed TGs from B. ruderatus, B. bohemicus, and B. campestris. Nonadec-9-ene and icos-15-en-1-ol are the main components of B. ruderatus labial gland secretion, forming up to 92% of the gland extract. The corresponding icos-11-enic and icos-15-enic acids were found in TGs at levels higher than usual for bumblebee species. We found similar relationships in B. campestris and B. bohemicus. These results suggest that FAs might be precursors of aliphatic compounds in the male pheromones. Furthermore, we report for the first time the pheromone structure of B. ruderatus males.